Análise da integração dos elementos da paisagem, por meio da conectividade de compartimentos físico-ambientais na Unidade de Gerenciamento de Recursos Hídricos Tietê-Jacaré - Trevisan, Diego Peruchi (Universidade Federal de São Carlos, 2021)
The landscape structure is modified mainly as a result between nature and society, which produce a configuration characterized by the fragmentation or connection between its elements. This structure reflects the influence of physical, biological, political, economic, and social forces. One of the most effective forms of regional planning in Brazil is through the Water Resources Management Units, which with the river basin committees, provide legal support for such units. The network community model is the area of scientific research that seeks to understand the complexity of the various systems, being an essential tool in local and regional planning and management, applied in different systems, such as road, hydrological and ecological. The objective of this study was to evaluate the urbans and natural landscapes performances indicators based on the integration of connectivity between road, hydrological, and landscape structural networks in the Tietê-Jacaré Hydrographic Basin - SP. This objective involved the environmental characterization of the landscape and the diagnosis of land use and land cover in 2007 and 2017, with an emphasis on the layout and connectivity of existing elements through the indices application of Integration, Spatial Syntax, Hydrological Connectivity, Ecological Connectivity, and metric indexes of Connectivity and Landscape Fragmentation. The Tietê-Jacaré Hydrographic Basin has a high potential for the development of agricultural activities, mainly due to the evidence of low slopes and the characteristics of the present soils, which were confirmed by the classification of land use and land cover, which demonstrated the predominance of such activities in all regions of the basin, also culminating in the expansion of the road network over the years, which is an essential factor for the flow of this production. The region had a 38.43% growth in the road network and a 22% increase in connectivity, with a 2.34% decrease in the drainage network and a 25.53% decrease in connectivity. The vegetation areas were reduced by 2.72%, with a reduction in the connectivity of 18.50%. Thus, considering the three factors analyzed, the average change in connectivity and fragmentation of the Tietê-Jacaré Watershed between 2007 and 2017 was 22.01%. The fragmentation and integration indexes, when expressing the state of configuration of the landscapes, were presented as crucial tools in the diagnosis aimed at the conservation of ecosystems, allowing precise analysis of the elements that compose them. These indices also allowed the comparison not only of the natural fragments but of all classes of land use, which is essential in regional planning, such as in the case of hydrographic basins. The indices also allowed the comparison not only of natural fragments but of all classes of land use and land cover, which is essential in regional planning, such as the case of watersheds. These evidenced the loss of environmental quality, along with the growth of negative impacts, with the reduction of vegetation areas and drainage network and increased the roads concentration. This resulted in reduced drainage and vegetation connections and increased road connections that eventually culminated in changes in connectivity patterns, having the classes of urban and as predominant. The concern is not only about the current situation of the region, but also with the trends that have solidified over the years, such as the loss of natural areas and changes in the pattern and organization of the landscape as a result of the expansion of human activities. The ecosystems, with their environmental goods and services, subsidize various anthropic and socioeconomic activities, and when overloaded beyond their carrying capacity, can compromise the fulfillment of human needs. In this way, the strengthening of participation spaces, through the mobilization of the population and their representativeness, should be a premise of the municipal, state and federal administration, for the formulation, execution, and monitoring of urban development plans, programs, and projects.
Analysis of the integration of the landscape elements through the connectivity of physical-environmental compartments in the Tietê-Jacaré Water Resource Management Unit
Keywords: Análise de redes; Conectividade da paisagem; Gestão da paisagem; Planejamento Regional; Network analysis; Landscape connectivity; Landscape management; Regional Planning; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL